Efficacy of prophylactic human papillomavirus vaccines on cervical cancer among the Asian population: A meta-analysis - Ren, Xinyu; Hao, Yubing; Wu, Beike; Jia, Xinhua; Niu, Meili; Wang, Kunbo; Li, Zhifang (Frontiers in Microbiology, 2022)
Objective: We conducted a meta-analysis to assess the efficacy of prophylactic human papillomavirus (HPV) vaccines against cervical cancer precursors and HPV persistent infection among Asian populations. Methods: Randomized controlled clinical trials conducted in Asian countries were identified from three electronic databases (PubMed, EMBASE and the Cochrane Library). Publication retrieval was performed on March 1, 2022, and only those written in English were included. The data were analyzed with Cochrane Review Manager (version 5.3) and Stata/SE (15.1). Effect sizes were presented as risk ratios (RRs) and 95% confidence intervals (CIs). Results: Eleven articles were considered in the meta-analysis, without significant heterogeneity among them. The fixed-effect RRs and 95% CIs for cervical intraepithelial neoplasia grade 1 (CIN1+) and CIN2+ were 0.10 (0.05-0.21) and 0.11 (0.04–0.27), respectively. Positive effect of HPV vaccination on 6- and 12-month persistent infection were observed, with the respective pooled RRs of 0.05 (95% CI: 0.03-0.09) and 0.09 (95% CI: 0.05-0.15). HPV vaccination has a positive effect on the incidence of cytological abnormalities associated with HPV 16/18 (RR, 0.13; 95% CI (0.09-0.20)). Positive effects of HPV vaccination were also observed for HPV 16- and 18-specific immunogenicity (RR, 235.02; 95% CI (82.77-667.31) and RR, 98.24; 95% CI (50.36-191.67), respectively). Females receiving an initial vaccination showed significant decreased incidences of cervical intraepithelial neoplasia, HPV persistent infection and cytological abnormalities and a significantly higher antibody positive conversion rate compared with non-vaccination counterparts. Conclusions: Prophylactic HPV vaccines are highly efficacious in preventing cervical cancer in Asian females. The government should accelerate the processes of vaccine introduction and vaccination implementation by prioritizing them in public health policies, which should be helpful to enhance Asian females’ awareness of receiving HPV vaccination volitionally.